Some insights into the screech tone of under-expanded supersonic jets using dynamic mode decomposition - Zang, B. (2022)
Jet screech is an intense pure tone which has attracted decades of research interest due to its possible detrimental effect on engineering structures. Its modes and closure mechanisms have been investigated analytically, experimentally, and numerically; however, there are still outstanding questions regarding the generation and propagation of instabilities in the near-field region. Recent studies have identified that these instabilities travel inside the jet potential during the screech process to form the complete feedback loop. Using dynamic mode decomposition on a three-dimensional pressure near field from large-eddy simulation results, the present study examines the viability of modal decomposition to provide further insights into the screech mode and its associated characteristics, and investigates the effect of temperature mixing in jet screech. The results show that modal decomposition identifies the helical structure of screech mode. Furthermore, a method is proposed to reveal the temporal evolution of dynamic screech mode. It was found that the bulk behavior of the pressure field at screech frequency propagates backward toward the nozzle exit.